A Continuous Improvement Instrument for the evaluationof the ergonomics management system in the supply chain - Rodríguez-Gámez, Iván Francisco; Maldonado-Macías, Aide Aracely; Hernandez Arellano, Juan Luis; Lagarda-Leyva, Ernesto A.; Rodríguez, Yordan (2024)
Nowadays, organizations must comply with high-quality standards, health and safety regulations, and socially sustainable practices to succeed in a globalized world. Supply Chains (SC) enable them to satisfy their customers’ needs for quality products just in time and at the best price. However, management systems (MS) need to be improved to identify, evaluate, and control er gonomic risks, which opens a research opportunity for Ergonomics Management Systems (EMS) as they apply to sustainable SCs. This study aims to design and validate an instrument to assess the EMS within a SC using a continuous improvement approach. The study used convenience sampling as experts were invited by e-mail, at congresses, and through a digital platform. A response rate of 6.2 % was obtained from the latter, and a total of 34 experts responded to the instrument. An exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA) were also carried out for the constructs of PLAN, DO, CHECK, and ACT. Finally, factors and variables were reduced by 42.71 %, leaving a 46-item final version of the instrument. Most of the structural model fit indices for the sample demonstrated good values, and the reliability indices were acceptable, this confirming the overall reliability of the instrument. In conclusion, the instrument was validated for all proposed constructs, with the exception of the PLAN construct. Thus, the instrument was found to be relevant and fit for implementation in EMS.